Genotypic variation in promotion of rice dinitrogen fixation as determined by nitrogen-15 dilution - Shrestha, R.K.; Ladha, J.K. (Wiley, 1996)
Rice (Oryza sativa L.) genotypes capable of stimulating associative N2 fixation (NFS) are desirable to reduce dependence on fertilizer N. A pot experiment was conducted during the 1993 dry season to assess differences in NFS among 70 genotypes of diverse origin and growth duration and to validate the use of 15N enrichment of mineralized soil N as reference for N2 fixation measurement. The soil used had a stable 15N enrichment that was obtained by incubating and frequent mixing with (15NH4)2SO4 (6.3 kg N ha−1) in submerged condition for 6 wk. The 15N enrichment of soil NH+4‐N dropped exponentially, showing an initial rapid decline to half of the original level within 2 wk, followed by a slower, nonsignificant rate of decline after 5 wk. Whole plant 15N atom % excess was inversely correlated with growth duration and ranged from 1.78 in Oking Seroni (late genotype) to 2.45 in PTB‐18 (early genotype). It was, therefore, necessary to compare NFS among genotypes of the same growth duration. Enrichment was lowest in the roots, suggesting this as the site of active N2 fixation; it was highest in the shoot and intermediate in grain. Nitrogen derived from air (Ndfa) estimated using 15N enrichments of mineralized soil N and reference rice genotype correlated highly (r = +0.998**). Percentage Ndfa ranged from 1.5 to 21.0, with an average of 10.2. Yelsulbyeo, Pankaj, and Oking Seroni had the highest Ndfa among early, medium, and long growth duration genotypes, respectively. Genotypes with high Ndfa, grain yield, and N uptake are Oking Seroni, IR29337‐36‐3, OR‐142‐99, and Pankaj.